Atributos funcionais de Odonata adultos associados a mudanças na vegetação ripária de riachos de cerrado - VIANA, Carolina Gomes (Universidade Federal do Oeste do Pará, 2024)
The capacity of species to adapt to different environmental gradients is essential for their survival, since the environment can present variations over space and time These variations provide conditions and resources for different species to establish and remain in certain places, since the potential to withstand these conditions is related to the existence of adaptable attributes necessary for survival. Thus, our study sought to understand the relationship between an environmental variation gradient and the functional structure of adult Odonata assemblages in riparian zones of the Cerrado. Data were collected from 50 streams in eastern Maranhão and western Piauí, between May 2021 and January 2022. Five functional attributes were considered: total length, thorax width, abdomen length, forewing length and width, and environmental variables: canopy cover, channel width and depth. A total of 1 .528 specimens of adult Odonata distributed in seven families, 30 genera and 74 species were collected. We found that more open areas or those with loss of vegetation had larger insects, with the cover of riparian vegetation adjacent to the channel being the main predictor of the structure of Odonata assemblages. As the size of organisms increases, their dependence on the sun's rays for heating also increases. Added to this, the selective pressure exerted by the environment drives the evolution and adaptation of wing shape in species. Thus, the selection of insects with specific characteristics is observed to the detriment of other groups according to the characteristics of the habitat. Additionally, this filtering can lead to the homogenization of biodiversity and loss of functionality in extreme or degraded environments, indicating that functional traits are relevant attributes for understanding the distribution of Odonata species, and that the conservation and proper management of riparian zones are indispensable to guarantee the survival of these species and of the different behavioral and ecophysiological groups that the order presents.